2023
DOI: 10.1038/s41420-023-01527-6
|View full text |Cite
|
Sign up to set email alerts
|

ROR1-STAT3 signaling contributes to ovarian cancer intra-tumor heterogeneity

Abstract: Wnt pathway dysregulation through genetic and non-genetic alterations occurs in multiple cancers, including ovarian cancer (OC). The aberrant expression of the non-canonical Wnt signaling receptor ROR1 is thought to contribute to OC progression and drug resistance. However, the key molecular events mediated by ROR1 that are involved in OC tumorigenesis are not fully understood. Here, we show that ROR1 expression is enhanced by neoadjuvant chemotherapy, and Wnt5a binding to ROR1 can induce oncogenic signaling v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Ovarian cancer (OV) is a disease with clinical diversity and high histological and molecular heterogeneity, 1 , 2 , 3 and its histological phenotype is associated with distinct genetic patterns. 4 Each subtype has a different histopathology and a different response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer (OV) is a disease with clinical diversity and high histological and molecular heterogeneity, 1 , 2 , 3 and its histological phenotype is associated with distinct genetic patterns. 4 Each subtype has a different histopathology and a different response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…S1P-S1PR1 signalling induces persistent activation of STAT3 and leads to chronic intestinal inflammation and development of colitis-associated cancer [ 8 ]. Interestingly, ROR1 expression is induced by STAT3 [ 9 ], which is in turn being activated by S1P. Additionally, S1PR1 trans-activates receptor tyrosine kinases [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has revealed that ROR1 is aberrantly overexpressed in several malignancies, such as lung cancer, breast cancer, and chronic lymphocytic leukemia (CLL). Upon Wnt5a stimulation, ROR1 activates multiple signaling transductions, including PI3K/AKT/mTOR, RAS/ERK, NF-κB, JAK/STAT, and/or Hippo pathways, which are involved in tumor progression and poor survival of patients by promoting cell proliferation, survival, and metastasis. Consequently, targeting ROR1 might be a potential cancer treatment approach. Some initial progress has been achieved in cancer treatment by ROR1-targeting monoclonal antibodies, antibody-drug conjugates (ADCs), CAR-T cells, and small-molecule inhibitors (Figure ).…”
Section: Introductionmentioning
confidence: 99%